2018
DOI: 10.1017/s0031182018001798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature onParamoeba peruransgrowth in culture and the associated microbial community

Abstract: Population growth, in vitro, of three Paramoeba perurans cultures, one polyclonal (G) and two clonal (B8, CE6, derived from G), previously shown to differ in virulence (B8 > G > CE6), was compared at 10 and 15 °C. B8 showed a significantly higher increase in attached and in suspended amoebae over time at 15 and 10 °C, respectively. CE6 and G also had significantly higher numbers of suspended amoebae at 10 °C compared with 15 °C at experiment termination. However, in contrast to B8, numbers of attached am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Similar letters indicate that different treatments were not statistically different (p > 0.05, n = 40) a significant difference between infected fish held at 10 and 15°C during the first, second and third samplings after P. perurans exposure with an earlier detection and higher numbers (or possibly higher expression activity) of P. perurans associated with the higher temperature (15°C). A recent study using the same P. perurans clone as in this study (B8) showed in vitro a significantly higher increase in attached amoeba over time at 15°C than at 10°C (while amoebae in suspension increased to a greater extent at 10°C), and this phenomenon perhaps contributes to the findings here (Benedicenti et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar letters indicate that different treatments were not statistically different (p > 0.05, n = 40) a significant difference between infected fish held at 10 and 15°C during the first, second and third samplings after P. perurans exposure with an earlier detection and higher numbers (or possibly higher expression activity) of P. perurans associated with the higher temperature (15°C). A recent study using the same P. perurans clone as in this study (B8) showed in vitro a significantly higher increase in attached amoeba over time at 15°C than at 10°C (while amoebae in suspension increased to a greater extent at 10°C), and this phenomenon perhaps contributes to the findings here (Benedicenti et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…Immune-and stress-related gene expression analysis showed modulation in gills rather than in head kidney, mainly during the first sampling point after challenge, with different expression levels between the two organs revealing an organ-specific response. Therefore, higher temperature (at 15°C) while linked mainly to earlier and stronger P. perurans infection through supporting greater proliferation of P. perurans on gills, at least for the amoeba clone used here (Benedicenti et al, 2019), may also act as a potential stressor in terms of changes in hormone levels in the plasma during early stages of pathology.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to the abundance of literature suggesting N. perurans microbiome may in uence AGD progression 26,27,29,30 , 16S rRNA sequencing was employed to clarify the role of the microbiome in the virulent and attenuated isolates. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several genera coupled to Pseudomonas spp, Marinomonas sp and Flavobacterium sp were identi ed 29 . Polygonal and clonal isolates of N. perurans shared several genera of both gram positive and gram negative bacteria with signi cant differences in relative abundances between the three isolates 30 . Despite the speculation surrounding the role of N. perurans microbiome in AGD, no study exists that directly compares the microbiome of a long-term cultured N. perurans isolate to a virulent isolate.…”
Section: Introductionmentioning
confidence: 99%